SEI Grown on MCMB-Electrode with Fluoroethylene Carbonate and Vinylene Carbonate Additives as Probed by In Situ DRIFTS. Issue 13 (1st January 2019) - Yohannes, Yonas Beyene; Lin, Shawn D.; Wu, Nae-Lih; Hwang, Bing-Joe
Abstract : The formation of solid electrolyte interphase (SEI) on electrodes of Lithium ion batteries (LiBs) is known to influence the electrochemical performance of LiBs. In this work, the effect of fluoroethylene carbonate (FEC) and vinylene carbonate (VC) on the SEI formation on mesocarbon microbeads (MCMB) anode is examined by in situ DRIFTS (diffuse reflectance infrared Fourier-transformed spectroscopy). Formation of SEI species on MCMB starts in the first lithiation cycle with an onset potential corresponding to the electrochemical reduction potential of the additive. However, both VC and FEC result in continuous SEI formation in subsequent cycles with no onset potential. Similar SEI species are found in the first lithiation cycle and in the subsequent cycles. This suggests the presence of an electrochemical initiation of SEI species formation with a subsequent propagation, similar with what we found previously over Si-based anode. [Y. B. Yohannes, S. D. Lin and N.-L. Wu, J. Electrochem. Soc., 164, A3641 (2017)] The contribution of the observed SEI species for the improved electrochemical impedances through cycling and its implications are discussed.